Digital Disconnection as an Opportunity for the Tourism Business: A Bibliometric Analysis - Juan F. Arenas-Escaso; José A. Folgado-Fernández; Pedro R. Palos-Sanchez (Ital Publication, 2022)
The aim of this study is to carry out a bibliometric review of the existing research on digital disconnection and Digital Free Tourism (DFT) to discover the extent to which this new trend affects technology users and the tourism market. To do this, a systematic literature review and a bibliometric analysis of the research on digital disconnection contained in the Scopus and Web of Science databases were used. This research includes publications from 2012 to December 2021, which included a total of 37 publications about digital disconnection and digital free tourism in scientific journals indexed in the main scientific databases. The analysis concludes that DFT is a growing economic trend in research and that the phenomenon of digital disconnection is beginning to be a peremptory need for more and more users. This work is original and interesting for researchers specialising in technology addictions, as well as academics and professionals in the tourism sector, because the extensive use of smart devices is becoming a type of addiction in many areas and can be a new opportunity for the tourism market. The DFT phenomenon can improve the response to these types of addictions and be a temporary escape and alternative to technological devices. Doi: 10.28991/ESJ-2022-06-05-013 Full Text: PDF